2018
DOI: 10.3390/joitmc4020019
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Innovation and New Product Portfolios. A Compositional Approach

Abstract: Product innovation performance is often measured by means of the percentages in the product portfolio from: (a) innovative products launched for the first time in the market; (b) new products to the firm already extant in the market; and (c) unchanged products. These percentages have often been used to assess the impact of open innovation. More recently, innovation in marketing mix has attracted interest per se, beyond the traditional role of marketing in providing external information about consumer needs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
1
23
0
1
Order By: Relevance
“…Likewise, trying to boost sales of products such as computers and accessories does not generate enthusiasm among users and is not perceived as an effective tactic by customers [65][66][67]. This fact must be carefully considered by company executives willing to participate in temporary events based on offers and discounts published on the Internet [68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, trying to boost sales of products such as computers and accessories does not generate enthusiasm among users and is not perceived as an effective tactic by customers [65][66][67]. This fact must be carefully considered by company executives willing to participate in temporary events based on offers and discounts published on the Internet [68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…External collaboration can help to achieve a proof-of-concept, thereby improving the usability of ideas, enabling faster development and market launch of new products or services, and decreasing costs by sharing R&D infrastructure and equipment. In particular, small and medium enterprises (SMEs), which generally do not have sufficient internal capabilities and resources for innovation, can obtain external knowledge and experience that are essential for technology innovation through open innovation [39,40]. Hau [41] investigated the relationship between open innovation and the technology commercialization capability of SMEs.…”
Section: Technology Commercialization Process and Open Innovationmentioning
confidence: 99%
“…Furthermore, intellectual property (IP) is controlled to ensure that competitors cannot use ideas for profit. However, recent research has identified the advantages of external knowledge and the negative perception of knowledge leakage between the company and the environment are disappearing [39,40]. Accordingly, a shift from closed innovation to open innovation is occurring.…”
Section: Technology Commercialization Process and Open Innovationmentioning
confidence: 99%
“…In the future, a huge number (80% of products that will be available in 2020, have not been invented yet [15]) of products will be developed and they will be brand new products; on the other hand, they are only about improving existing products, which, despite the same or somewhat modified mode of operation, continuously satisfy consumers. Whether the individual, or products of broader production, the fact is that the need to keep them is constantly emerging.…”
mentioning
confidence: 99%